IMPROVING THE INVESTMENT CLIMATE IN UZBEKISTAN SOME IMPORTANT ISSUES - Imomov Xamdilla Xamdamovich (Scholar Express Journals, 2025)
The article highlights some important issues in creating an environment of attractiveness by improving the investment environment in Uzbekistan and implementing the investment opportunities available in the country.
Keywords: Capita; investment; foreign investment; production